Research on the Criteria for Determining the Starting Performance of an Inward-Turning Inlet by Integrating the Concept of the Equivalent Contraction Ratio - Fanshuo Meng; Bo Jin; Xiaolong He; Zheng Chen; Wenhui Yan; Zhenjun Zhao; Zonghan Yu (Aerospace)
The prediction of hypersonic inlet starting performance is crucial for the successful ignition of the combustion chamber, directly impacting the overall performance of the propulsion system. This challenge arises especially when freestream conditions vary. Therefore, this paper proposes the concept of the equivalent contraction ratio, and establishes and analyzes the intrinsic correlation between the geometric contraction ratio and angle of attack on the starting performance of three-dimensional inward-turning inlet. The results indicate the following: (1) The startability index can be applied to determine the start boundary of the three-dimensional inward-turning inlet under conditions of the freestream Mach number of 6.0 and an altitude of 27 km, with a deviation of no more than 6.6% from the optimal SI = 0.087 criterion; (2) The start boundary after applying the equivalent contraction ratio shows deviations not exceeding 4.0% under positive angle-of-attack conditions compared to the startability index, while the deviation is larger under negative angle-of-attack conditions, reaching a maximum of 13.3%. After applying a correction formula, the deviations can be reduced to within 2.0%; (3) For the same equivalent contraction ratio, the differences in starting performance between different positive and negative angle-of-attack conditions may fundamentally arise from the degree of compression of the inlet. Finally, the equivalent contraction ratio theory is proven to be able to quickly and easily predict the accurate starting performance of the inward-turning inlet at different angles of attack, improving the breadth and efficiency of engineering predictions.